Sustainable buildings - Green, Elisabeth; Hope, Tristram; Yates, Alan (Delivering sustainable infrastructure., 2015)
'Sustainable Buildings' is an indispensable handbook that combines a summary of good practice and sources of information helpful to practitioners involved in the design and procurement of buildings. This book illustrates the need for inter-disciplinary integration and an understanding of environmental physics as early as possible in the design process in order to deliver high-quality, economical and sustainable infrastructure across the globe.